732 A daily diary study of nightmare reports among combat-exposed Veterans. (3rd May 2021) - Miller, Katherine; Goldstein, Elly; Barilla, Holly; Carroll, Rain; Ross, Richard; Kling, Mitchel; Bhatnagar, Seema; Gehrman, Philip
Abstract: Introduction: Nightmare occurrences may, in part, result from prior-day arousal (e.g., the continuity hypothesis), and that they then influence next-day symptoms. Recent ecological momentary assessment (EMA) studies in samples of civilian trauma survivors found that elevated PTSD symptoms, pre-sleep cognitive arousal, and greater sleep onset latency predicted nightmare reports. This study adds to these works by using EMA in a sample of combat-exposed Veterans. Methods: Data were analyzed from a study examining neurobiological and neuropsychological factors associated with PTSD in a sample of 27 combat-exposed OEF/OIF Veterans, with and without PTSD. Participants engaged in EMA for 6 days, with assessments across the day inquiring about mood, activity, and stressful events. Morning reports also included the consensus sleep diary and prompts on nightmare experiences. Those reporting nightmares were asked about nightmare disturbance and the level of replicability to a traumatic event (replays or symbolic/unrelated). Multi-level modeling analyses were used. Results: A total of 113 morning reports were acquired, in which 40 included a report of having a nightmare and 73 did not. Main effects were found for baseline PTSD symptom severity (OR=1.13, p=0.02), prior day time spent alone (OR=0.01, p=0.01) and prior day level of distraction (OR=0.25, p=0.02) on morning reports of nightmares. However, when accounting for the previous night's nightmare report (OR=15.9, p<0.001), these effects were no longer significant. No other effects on nightmare reports were observed. Additionally, no factors predicted replicability of nightmare content or level of nightmare disturbance. Regarding daytime impact, nightmare reports were associated with greater levels of stress associated with events later that day (OR=2.48, p=0.04). Conclusion: Greater baseline PTSD symptom severity, less daytime spent alone, and greater daytime attentiveness were significant predictors of nightmare reports. While daily social interactions and attentiveness may be beneficial, these factors also may be associated with hypervigilance, a known risk for sleep disruption. However, these data also suggest that day-to-day levels of stress may have less influence when a chronic nightmare pattern is present. Support (if any): Defense Advanced Research Projects Agency under a grant from the U.S. Army Research Office (W911NF1010093). U.S. Department of Veterans Affairs, Veterans Health Administration (CSR&D- IK2 CX001874).